Sweet Geometry: Edward Reynolds at the Architectural Association, 1956–58. (2019) - Franklin, Geraint
Abstract: This article considers the position of the Anglo-Portuguese architect Edward Reynolds (1926–59) in the British avant-garde of the 1950s. In Modern Architecture: A Critical History (1980), Kenneth Frampton suggested that Reynolds's student projects at the Architectural Association in London 'exerted a decisive influence on the development of Brutalism'. This article scrutinises that claim through the lens of Reynolds's interactions with his peers, including the so-called French House group, an informal network that included his tutors John Killick, James Gowan and Peter Smithson. Notable characteristics of Reynolds's work — chiefly the use of complex and irregular geometries to articulate patterns of activity and movement — are discussed, as are contemporary projects by other members of the group and trends such as the New Brutalism, biomimicry and the revival of pre-war strands of Modernism.